Solid‐State Structure of Protonated Ketones and Aldehydes. (29th November 2017) - Stuart, Daniel; Wetmore, Stacey D.; Gerken, Michael
Abstract: Protonated carbonyl compounds have been invoked as intermediates in many acid‐catalyzed organic reactions. To gain key structural and electronic data about such intermediates, oxonium salts derived from five representative examples of ketones and aldehydes are synthesized in the solid state, and characterized by X‐ray crystallography and Raman spectroscopy for the first time. DFT calculations were carried out on the cations in the gas phase. Whereas an equimolar reaction of the carbonyl compounds, acetone, cyclopentanone, adamantanone, and acetaldehyde, with SbF5 in anhydrous HF yielded mononuclear oxonium cations, the same stoichiometry in a reaction with benzaldehyde resulted in formation of a hemiprotonated, hydrogen‐bridged dimeric cation. Hemiprotonated acetaldehyde was obtained when a 2:1 ratio of aldehyde and SbF5 was used. Experimental and NBO analyses quantify the significant increase in electrophilicity of the oxonium cations compared to that of the parent ketones/aldehydes.